1988
DOI: 10.1037/0022-0167.35.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Afro-American preferences for counselor characteristics: A replication and extension.

Abstract: This study replicates and extends the Atkinson, Furlong, and Poston (1986) investigation that examined Black subjects' preferences for salient similar and dissimilar counselor characteristics within a disconfirmatory hypothesis-testing strategy framework. Using a markedly different Black college student sample and replicating the paired-comparison technique of , the present study found a generally high rank-order correlation (p = .91) between the two respective samples on preferences for counselor characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…Hence, a bicultural person may display some host culture behaviors (for example, in gender role behaviors), while retaining other parent culture behaviors (for example, behaviors toward elders and parental authority). The variable of acculturation has an important role in promoting the understanding of ethnic minority issues, because it is associated with patterns of conflict resolution (Kagan, Zahn, & Geasly, 1977), attitude toward counselors (Atkinson & Matsushita, 1991;Parham & Helms, 1981;Pomales & Williams, 1989;Ponterotto, Alexander, & Hinkston, 1988). willingness to use counseling services (Sanchez & Atkinson, 1983).…”
mentioning
confidence: 99%
“…Hence, a bicultural person may display some host culture behaviors (for example, in gender role behaviors), while retaining other parent culture behaviors (for example, behaviors toward elders and parental authority). The variable of acculturation has an important role in promoting the understanding of ethnic minority issues, because it is associated with patterns of conflict resolution (Kagan, Zahn, & Geasly, 1977), attitude toward counselors (Atkinson & Matsushita, 1991;Parham & Helms, 1981;Pomales & Williams, 1989;Ponterotto, Alexander, & Hinkston, 1988). willingness to use counseling services (Sanchez & Atkinson, 1983).…”
mentioning
confidence: 99%
“…Information concerning the preferences of African American, Asian American, Mexican American, and American Indian college students for this expanded range of counselor attributes is now available. For these groups, results suggest that counselor race or ethnicity is of less importance than other characteristics, such as the counselor's educational level or the similarity of the counselor's attitudes and values to that of the client (Atkinson et al, 1986; Atkinson, Poston, Furlong, & Mercado, 1989; Bennett & BigFoot-Sipes, 199 1 ; Ponterotto, Alexander, & Hinkston. 1988).…”
mentioning
confidence: 99%
“…Both counselors were about the age of the members' mothers. Research by Ponterotto et al (1988) found that the African American male students ranked preference for an opposite-sex counselor higher than for a samesex counselor. The researchers state that this preference may be due to the tendency of men and women in the United States to prefer a woman as a source of emotional support.…”
Section: Discussionmentioning
confidence: 95%
“…However, with the disproportionate number of European American counselors in many school systems, African American students need not be deprived of their own groups. In addition, although caution has been advised in the interpretation of the findings, research studies on older students have consistently concluded that African Americans generally prefer counselors of the same race (Coleman, Wampold, & Casali, 1995;Ponterotto, Alexander, & Hinkston, 1988;Terrell & Terrell, 1984;Watkins & Terrell, 1988).…”
Section: Discussionmentioning
confidence: 96%